PARTNERSHIP-DUAL TRAINING SYSTEM MODEL FOR BASIC SAFETY TRAINING TO IMPROVE VOCATIONAL EDUCATION TEACHER COMPETENCE - Kisno; Saut Purba; Arif Rahman; Sherly; Selviana Napitupulu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract